Propuesta de un diseño de control interno bajo la metodología COSO I, para la administración de inventarios en la empresa distribuidora Vibohogar S.A.S. de la Ciudad de Palmira (Valle del Cauca) - Cortés Tolosa, Robinson (Universidad Antonio Nariño, 2022)
When a company is created, such as Distribuidora VIBOHOGAR SAS, the owners and managers are generally the same people, who initially limit themselves to complying with the regulations required by control entities for the opening of new companies, such as the Chamber of Commerce, achieving in this way, start with the operation of it. They also focus their efforts on the way in which the products will be marketed, the pricing and the employees to be hired.